Incipity recenzji publicystycznych, czyli j ak rozpocząć ocenę filmu - Krauz, Maria (Słowo. Studia językoznawcze, 2012)
The research concentrates on the incipits of film reviews found in professional journals and reviews. The author discusses the ways of starting a review and the function of initial sentences. In the analyzed texts there have been specified and discussed two types of beginnings: neutral one, typical for the given genre, and modified one, having a persuasive function. The first group includes statements with metatextual formulas, general semantically complete statements (informing us about the subject, film director, description of the main character), or brief summaries. The modified beginnings, which are aimed at intriguing the readers, are, among others, brief emotive evaluations, and intertextual play characteristic also for other publicistic genres.